INFLUENCE OF ELECTRONIC WORD OF MOUTH AND INFLUENCER IN THE USE OF INSTAGRAM ON PURCHASING INTENTION ON WOMEN’S APPAREL - EKO FITRIANDRI; MIA KIRANA; DESI NURFATMASARI; SANI DNAR SAIFUDDIN (CV KULTURA DIGITAL MEDIA, 2021)
This research aims to examine the influence of electronic word of mouth and influencers in the use of Instagram account shopee_id on purchasing intention of women's apparel among shopee_id IG followers. Currently, Instagram has become one of the most popular social media for marketing activities, especially during the pandemic period in the past two years. Many people hold online transactions there. The electronic word of mouth and influencers on Instagram, in building the brand images of the products offered by shopee_id, especially women's apparel products, play important roles in strengthening consumers’ purchasing intention or buying interest. This research uses Electronic Word of Mouth and Influencer Research variables on the Instagram account of @shopee_id and Purchasing Intention of women's apparel among female @shopee_id followers. The sampling is carried out using the Non Probability - Convenience / Accidental Sampling technique. The research also uses Quantitative Approach, Postpositive Perspective, and Correlational Survey Method to test three research hypotheses: “Electronic Word of Mouth Influences Purchasing Intention”, “Influencers Influences Purchasing Intention”, and “Electronic Word of Mouth and Influencers Together Influences Purchasing Intention”. Based on data processing and analysis using SPSS, it can be concluded from the first hypothesis testing that there is a significant positive effect of e-WOM on Purchasing Intention. The result of the second hypothesis testing shows that there is a significant positive effect of Influencers on Purchasing Intention. The result of the last hypothesis testing concludes that there is a significant positive effect of e-WOM and Influencers together on Purchasing Intention.